Chapter 11. Legume Production - Craig Frey; Peter J. Dittmar; Dakshina R. Seal; Shouan Zhang; Josh H. Freeman; Johan Desaeger; Qingren Wang (EDIS, 2021)
Chapter 11 of the Vegetable Production Handbook.